2015
DOI: 10.5455/ijmsph.2015.30012015196
|View full text |Cite
|
Sign up to set email alerts
|

Initial default among tuberculosis patients diagnosed in selected medical colleges of Puducherry: issues and possible interventions

Abstract: Background: India accounts for one-fourth of the global incident tuberculosis (TB) case load and tops the list of highburden countries. Initial default and loss to follow-up are important challenges in achieving the objectives of the Revised National TB Control Programme (RNTCP). Objective: A study was carried out to estimate the proportion of initial defaulters, reasons for initial default, and recommendations to reduce initial default. Materials and Methods: A record-based study was carried out to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…Of these, 14 contain relevant data on pretreatment loss to follow-up of smear-positive TB patients [4446,60,62–71], and two studies contain data on pretreatment loss to follow-up of MDR TB patients [47,48]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 14 contain relevant data on pretreatment loss to follow-up of smear-positive TB patients [4446,60,62–71], and two studies contain data on pretreatment loss to follow-up of MDR TB patients [47,48]. …”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies provide specific information on the proportion of pretreatment loss to follow-up patients who are lost during the referral process. These studies report that 98/120 (81.6%) [44], 62/63 (98.4%) [45], and 75/145 (51.7%) [46] of pretreatment loss to follow-up among smear-positive patients occurred during referral, for a pooled prevalence of 235/328 (71.6%, 95%CI: 66.5%–76.3%). The pooled prevalence of the two studies of MDR TB patients shows a pretreatment loss to follow-up rate of 23.0% (95%CI: 21.8%–24.3%) (Table H in S3 Text).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that high indirect costs, the anticipated/real side effects of TB treatment and the non-acceptance of TB diagnoses were major inhibitors to treatment initiation and therefore initial LTFU. Two studies from India [9, 10] both used semi-structured interviews for patients enrolled in the Revised National Tuberculosis Control Programme and found alcoholism, TB-related stigma, lack of TB awareness, lack of support and the fact that patients were busy with “other jobs” main contributors to initial LTFU. Therefore the reasons for initial LTFU appear varied and context specific, with extensive gaps remaining in understanding why it occurs and what the possible enablers and inhibitors are to having patients initiate treatment.…”
Section: Introductionmentioning
confidence: 99%